Exploring family language policy in action: Child agency and the lived experiences of multilingual Ethiopian and Eritrean families in Sweden - Degu, Yeshalem Abraham (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Existing family language policy (FLP) scholarship has been criticised for insufficiently addressing children’s voices and perspectives on their multilingual experiences, as well as lacking representation and heterogeneity in terms of studies involving multilingual families from diverse family types, languages, and contexts outside the experiences of Western middle-class bilingual families. Against this backdrop, this paper examines the multilingual familial experiences of three Ethiopian and Eritrean migrant families in Sweden by paying particular attention to children’s agency and caregiver-children dynamics in FLP making. The study draws on multimodal biographic data obtained from children and parents through language portrait methods of body and space mapping activities, post-mapping narration, and semi-structured interviews. The data are analysed in light of Smith-Christmas’s (2020) framework, which views child agency in FLP at the intersection of compliance regime, linguistic competence, linguistic norms, and power dynamics. The findings reveal that the process of FLP making is characterised as a process that is (1) filled with language choice dilemmas triggered by competing linguistic demands, (2) in part shaped by the family constellation via power dynamics between family members, and (3) mediated by family members’ varied linguistic proficiencies in majority and minority languages. Additionally, children’s agency about which language they choose to use impacts the language practices of the home, as they tend to establish their own linguistic norms within the home by overrunning the negotiated language policy set by caregivers.